2006
DOI: 10.1152/ajpregu.00378.2005
|View full text |Cite
|
Sign up to set email alerts
|

In ovo exposure to monochromatic green light promotes skeletal muscle cell proliferation and affects myofiber growth in posthatch chicks

Abstract: Our previous studies demonstrated that illumination of chicken embryos with monochromatic green light results in enhanced body and muscle weight at later posthatch stages. In the present study, we investigated the cellular and molecular basis of this phenomenon. First, we showed that on day 6 posthatch, myofibers were more uniform in the in ovo illuminated group than in the control group incubated in the dark, with respect to the number of myofibers displaying diameter values within the range of the mean value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 45 publications
(63 reference statements)
5
77
1
2
Order By: Relevance
“…Rearing broiler chickens under blue light and green light showed higher carcass weight, carcass percent, and lower liver percent compared to white light group this may be attributed to improved quality and antioxidation process of muscles (Ke et al, 2011) and increased proliferation of skeletal muscle satellite cells (Halevy et al, 2006).…”
Section: 2carcass Traits and Weight Of Internal Organsmentioning
confidence: 93%
See 1 more Smart Citation
“…Rearing broiler chickens under blue light and green light showed higher carcass weight, carcass percent, and lower liver percent compared to white light group this may be attributed to improved quality and antioxidation process of muscles (Ke et al, 2011) and increased proliferation of skeletal muscle satellite cells (Halevy et al, 2006).…”
Section: 2carcass Traits and Weight Of Internal Organsmentioning
confidence: 93%
“…The improvement of final body weight and weight gain in broilers reared under blue and green light may be attributed to higher proliferation of skeletal muscle satellite cells (Halevy et al, 2006). While, much feed intake and inferior FCR in broiler reared under blue light and green light compared to white light treatment may be attributed to calming effect of blue and green light where, birds become less active (Mohamed et al 2014) and less stressful (Mohamed et al, 2016).…”
Section: Growth Performancementioning
confidence: 98%
“…Previous research has observed that exposing chicken (Rozenboim et al, 2004;Zhang et al, 2016) and turkey (Rozenboim et al, 2003) embryos to green light during incubation resulted in chicks with greater BWs and breast muscle weights. Halevy et al (2006) concluded that this increased growth due to green light exposure was due to enhanced proliferation and differentiation of adult myoblasts and myofiber synchronization. Zhang et al (2014) also saw that green light exposure during incubation enhanced proliferation and differentiation of satellite cells.…”
Section: Introductionmentioning
confidence: 99%
“…Organs involved in thermoregulation (hypothalamus, thyroid, and pituitary gland) develop during growth phase, but their final maturation occurs in the last days of incubation and shortly after hatching (FLORES et al, 2013 Different temperatures during incubation may have different effects on broiler weight after hatching, and may affect the final slaughter weight (TONA et al, 2004;WILLEMSEN et al, 2008); these variations may also increase tolerance to environmental temperature challenges (MORAES et al, 2003;COLLIN et al, 2007), alter post-natal growth (COLLIN et al, 2005;HALEVY et al, 2006), and resulted in improved performance on site at 38 days of age (SHINDER et al, 2009). These long-term adaptations occur after application of periodic thermal manipulation during the last phase of maturation, when embryos are most responsive to "training" (TZSCHENTKE & HALLE, 2009).…”
Section: Introductionmentioning
confidence: 99%